1998
DOI: 10.1016/s0893-133x(97)00090-0
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Proton Magnetic Resonance Spectroscopic Imaging in Patients with Schizophrenia

Abstract: Using proton magnetic resonance spectroscopic imaging ( 1 H-MRSI) we found in a previous study a specific pattern of neuronal pathology in patients with schizophrenia as determined by relative loss of signal from N-acetylcontaining compounds (NAA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 37 publications
3
28
2
Order By: Relevance
“…Deicken et al (2000) reported a decreased NAA signal in the mediodorsal region of the thalamus in schizophrenic patients. The authors pointed out that the discrepancy between their findings and previous MRSI studies (Bertolino et al 1996(Bertolino et al , 1998b) may be the result of differences in voxel selection. We could corroborate the finding of decreased NAA in the selected voxels of the mediodorsal region of the thalamus in schizophrenic patients ).…”
Section: S Thalamusmentioning
confidence: 63%
See 3 more Smart Citations
“…Deicken et al (2000) reported a decreased NAA signal in the mediodorsal region of the thalamus in schizophrenic patients. The authors pointed out that the discrepancy between their findings and previous MRSI studies (Bertolino et al 1996(Bertolino et al , 1998b) may be the result of differences in voxel selection. We could corroborate the finding of decreased NAA in the selected voxels of the mediodorsal region of the thalamus in schizophrenic patients ).…”
Section: S Thalamusmentioning
confidence: 63%
“…(Hazlett et al 1999) point out that morphologic changes of the thalamus in schizophrenia are only marginal but there are pronounced functional changes very localized to subregions of the thalamus, most pronounced in the mediodorsal nucleus. Whereas Omori et al (2000) and Deicken et al (2000) found a significant bilateral reduction in the thalamus of the NAA signal and ratio, Bertolino et al (1996Bertolino et al ( , 1998b and Delamillieure et al (2000) did not find significant differences between schizophrenic patients and controls in the thalamus. In a single voxel study, Heimberg et al (1998) found a trend towards reduced NAA in the left thalamus.…”
Section: S Thalamusmentioning
confidence: 88%
See 2 more Smart Citations
“…Reductions of NAA in the hippocampal area and the dorsolateral prefrontal cortex, suggestive of neuronal involvement, have been reported in adultonset schizophrenia and found to be independent of treatment [27,28]. Similarly, studies of children and adolescents with schizophrenia have shown reductions of NAA/Cre in the frontal lobes [29•,30] and mesial temporal regions [29•].…”
Section: Selected Functional Neuroimaging Findings In Child Psychiatrymentioning
confidence: 93%